Hubungan Antara Manajemen Waktu Dengan Prokrastinasi Akademik Siswa Smk Negeri 9 Padang - Nur Syahadani Putri; Yusri Fajra Syahril; Habibaturrahmah Habibaturrahmah (LPPM Universitas Dharma Andalas, 2022)
This study examines the relationship between time management and academic procrastination of class X students of SMK N 9 Padang for the 2019/2020 academic year. The method used in this research is quantitative with the type of research that is correlational. This study population numbered 418 people registered in the 2019/2020 school year. The sampling technique used was Proportional Random Sampling, in order to obtain a sample size of 205 people. Based on. The instrument used in data collection in this study was a questionnaire arranged according to the Likert scale model. Data analysis was performed using statistical programs on thecomputer IBM Statistical 20 and Microsoft Excel. Based on the results of the hypothesis the value of rcount is 0.431 while the value of rtable is 0.138 because the value of rcount is greater than the value of rtable (0.431> 0.138), it is concluded that there is a significant relationship with a positive direction between time management and academic procrastination.